1985
DOI: 10.1002/cyto.990060202
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different focus functions for use in autofocus algorithms

Abstract: A number of functions for the autofocusing of microscopes and other optical instruments are to be found in the literature. In this article we compare 11 of them to determine, in an objective manner, which functions are most suitable for implementation with real-time video acquisition systems. Three different images, each representing a typical class of imAutofocus algorithms are of particular importance in scanning microscope systems. The focus may have to be adjusted when the system mechanically moves from fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
310
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(321 citation statements)
references
References 8 publications
4
310
0
Order By: Relevance
“…From the work in [8,13,17,20,25], it is shown that most focus measures try to measure image properties like gray level image gradients, image contrast or frequency content. In essence they are a measure of the extent of the blur in the image.…”
Section: Focus Measurementioning
confidence: 99%
“…From the work in [8,13,17,20,25], it is shown that most focus measures try to measure image properties like gray level image gradients, image contrast or frequency content. In essence they are a measure of the extent of the blur in the image.…”
Section: Focus Measurementioning
confidence: 99%
“…Therefore, autofocusing is a fundamental technology for automated micromanipulation, and its essential technique is the focus measure. A variety of spatial focus measures have been proposed (Groen et al 1985;Firestone et al 1991;Subbarao et al 1993). These three focus measures, namely normalized variance (M V ), entropy (M E ), and energy laplace (M L ), have been reported as the classic and popular focus measures.…”
Section: A New Wavelet-based Focus Measurementioning
confidence: 99%
“…There is a good deal of literature on the subject of autofocus for microscopy and robotics in general (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Fitted with a video or digital camera and a motorized stage under computer control, the typical autofocus microscope system uses two complementary algorithms to achieve focus.…”
mentioning
confidence: 99%
“…Groen et al (11) and Boddeke et al (7) established criteria for validating a focus function: it must be accurate, reproducible, computationally efficient, unimodal (having only one maximum), and of sufficient range that focus may be found from a distance. Boddeke et al (7) used a model of image formation to show that the optimal spatial filter for a focus function would sample the middle frequencies passed by the optical system.…”
mentioning
confidence: 99%
See 1 more Smart Citation